2006
DOI: 10.1364/oe.14.003547
|View full text |Cite
|
Sign up to set email alerts
|

Color-selecting reflectors inspired from biological periodic multilayer structures

Abstract: We propose a semi-infinite 1-D photonic crystal approach for designing artificial reflectors which aim to reproduce color changes with the angle of incidence found in biological periodic multilayer templates. We show that both the dominant reflected wavelength and the photonic bandgap can be predicted and that these predictions agree with exact calculations of reflectance spectra for a finite multilayer structure. In order to help the designer, the concept of spectral richness of angle-tuned color-selecting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 4 publications
1
29
0
Order By: Relevance
“…Similar layered structures have been demonstrated to exist in other Buprestidae, e.g. the jewel beetles Chrysochroa vittata [6,7], Chrysochroa fulgidissima [8,9] and Chrysochroa raja [10].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar layered structures have been demonstrated to exist in other Buprestidae, e.g. the jewel beetles Chrysochroa vittata [6,7], Chrysochroa fulgidissima [8,9] and Chrysochroa raja [10].…”
Section: Introductionsupporting
confidence: 64%
“…Previous optical studies of the iridescence of jewel beetles have attempted to establish a quantitative description of measured reflectance spectra using multilayer modelling [8,10] and furthermore have shown that the beetles' photonic structures can inspire biomimetic applications [6]. Here, we extend the previous work by presenting a comprehensive set of reflectance spectra, measured as a function of angle and polarization.…”
Section: Introductionmentioning
confidence: 68%
“…Theory predicts that varying the angle of incidence of light falling on a multilayer reflector should result in a gradual shift of the dominant reflected wavelengths (Huxley, 1968;Land, 1972;Deparis et al, 2006). It has been shown in several squid species that, at least for the mantle area, altering the illumination angle does shift the reflectance and polarization spectra in a predictable way (Mäthger and Denton, 2001;.…”
Section: The Properties Of Polarized Light Reflections Partial Polarimentioning
confidence: 99%
“…For instance, butterflies, beetles, birds and even aquatic systems utilize the optical properties of one, two, and three-dimensional photonic crystals to enhance and control display or crypsis [12][13][14]. One-dimensional systems include the multilayer structure of many species of beetle [8,15,16], butterflies [17] and fish [18]. Two-dimensional structures include the two-dimensional hexagonal structure found in the polychaete worm [19].…”
Section: Introductionmentioning
confidence: 99%